Improving madrasah teachers' competence in managing learning modules through workshops at MI Arrasyidin and MI Al-Islam Magelang - Achmad Syakur (Yayasan Azhar Amanaa Yogyakarta, 2024)
Educators at MI Arrosyidin dan MI Al Islam Magelang must possess the ability to plan creatively inspiring and motivating learning experiences for students. Initial observations at the school have indicated that the implementation of the Self-Curriculum Teaching Module does not meet the expectations of many stakeholders. Therefore, MI Arrosyidin dan MI Al Islam Magelang, both in the context of online and offline learning, has decided to conduct research in 2024, between July and August. In this study, 16 teachers from MI Arrosyidin dan MI Al Islam Magelang are participating. This research takes the form of a school action research, a form of self-reflection commonly carried out by educational practitioners within the educational environment to improve the quality of education, gain a deeper understanding of teaching practices, and seek improvements in educational implementation. Data are collected through interviews, observations, and documentation. Based on the results of this research, it can be concluded that the training provided by the workshop facilitators has the potential to enhance teachers' ability to design Self-Curriculum Teaching Modules. One of the success indicators measurable in this school action research is that 95% of the teachers have successfully created Self-Curriculum Teaching Modules with a high level of creativity and innovation.